Analysis of Psycological Disorder Tedency for Polygamous Women Reproductive Health in Pamekasan Madura - Emi Yunita; Byba Melda Suhita; Koesnadi Koesnadi (Journal for Quality in Public Health, 2020)
The majority of polygamous marriages in Indonesia are only based on law and religion, regardless of the effects of polygamy. The lack attention public about the psychology that occurs in polygamous women. While, the impact of psychological disorders itself can affect to female hormones that can be caused to a reproduction system. The reproductive system can also experience disorders due to illness or abnormalities. The diseases of the reproductive system can be caused by germs, genetic factors, or hormones. Women have complex problems around their reproductive lives. Disorders of the female reproductive system can include menstrual disorders, vaginal cancer, cancer cervix, ovarian cancer, genetalia cancer, endometriosis, vaginal infections, vaginal discharge or fluorine, and Ghonorrhea. The purpose of this study is to explore the occurrence of psychological disorders that affect the reproductive health of polygamous women. The research design used is qualitative research with a phenomenological approach. The data collection in this study used in-depth interview techniques with semi-structured questions with a sample of 10 informants. From the results of the study indicate that the analysis of psychological disorders that have an impact on women's reproductive health in polygamy has good benefits for health workers and for the community, especially women. In analyzing the tendency of psychological disorders that affect the reproductive health of women who are polygamous there are many things that can be used as references on how the effects of polygamous marriages are related to women's reproductive health, both negative and positive impacts. In analyzing the trends of production in polygamous women there are some hopes of supporting improvements in public health, especially women's reproductive health. Based on this research, further research is needed on the analysis of trends in the occurrence of psychological disorders that have an impact on reproductive health in polygamous women in Pamekasan Madura